Individual and sex differences in frontloading behavior and approach- avoidance conflict preference predict addiction-like ethanol seeking in rats - Tanner A. McNamara; Hanyi Weng; Hsin Yu Liao; Rutsuko Ito (Scientific Reports)
Abstract Recent research has identified sex-dependent links between risk taking behaviors, approach-avoidance bias and alcohol intake. However, preclinical studies have typically assessed alcohol drinking using a singular dimension of intake (i.e. drinking level), failing to capture the multidimensional pattern of aberrant alcohol-seeking observed in alcohol use disorder. In this study, we sought to further explore individual and sex differences in the relationship between approach-avoidance bias, frontloading (bingeing and onset skew) and multiple addiction-like indices of ethanol seeking that included motivation for ethanol, persistence despite its absence (extinction), and ethanol-taking in the face of mild footshock. We found that female rats displayed more addiction-like phenotypes than males overall, and that frontloading patterns differed by sex, with females outdrinking males in the early part of access sessions (bingeing), but males strongly concentrating their lever pressing for ethanol in that period (onset skew). Multiple regression analyses revealed that bingeing was a strong positive predictor and onset skew a negative predictor of motivational breakpoint. Cued-conflict preference – a measure of approach-avoidance bias towards a mixed-valence conflict cue – was predictive of both extinction and footshock in males, but not females. Our data highlight key sex differences, and the relevance of both frontloading patterns and conflict preference in predicting future addiction-like phenotypes.